Clinical significance and underlying mechanism of long non‐coding RNA SNHG12 in lower extremity deep venous thrombosis - Shun Xiao; Chong Wang; Yongxin Li; Kun Zhang; Xuefei Jiao; Zonggang Zhao; Mingjin Guo; Bing Liu (Wiley, 2024)
Abstract D‐dimer is widely used in the diagnosis of deep vein thrombosis (DVT), but the specificity is low. The study examined the diagnostic value of long non‐coding RNA (lncRNA) SNHG12 in DVT, and preliminarily discussed its mechanism. SNHG12 levels were detected in 200 elderly fracture patients via RT‐qPCR, including 38 DVTs. Logistic regression analysis and receiver operating characteristic (ROC) curve were applied for diagnostic value evaluation. HUVECs were used for function study. Cell proliferation, migration, apoptosis, release of inflammatory cytokines, and adhesion factors were detected. Student's t test and one‐way ANOVA were applied for data comparison between two or among three or more groups. Correlation analysis of indicators was completed via Pearson's correlation analysis. Bioinformatics analysis predicted the target miRNAs and genes of SNHG12, with GO and KEGG for the function enrichment. It was found that SNHG12 was at low expression in DVT patients, and negatively correlated with D‐dimer concentration (r = −0.535). SNHG12 and D‐dimer were independent influence factors related to the development of DVT. SNHG12 and D‐dimer combination had the best performance in DVT diagnosis. In HUVECs, SNHG12 promoted cell proliferation and migration and restricted the release of inflammatory cytokines and adhesion factors, but these influences were counteracted by miR‐424‐5p. A total of 208 overlapping target genes of miR‐424‐5p were identified, and their function was enriched in cellular cycle and senescence. PI3K‐Akt signaling pathway was the most significant pathway based on KEGG results. In conclusion, SNHG12 had good diagnostic potential for DVT combined with D‐dimer. SNHG12 maintains vascular endothelial cell function by acting as a competitive endogenous RNA (ceRNA) for miR‐424‐5p.